2-2 - Chapter 2.2: Gauss-Jordan Elimination Unique...

Info iconThis preview shows pages 1–4. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Chapter 2.2: Gauss-Jordan Elimination Unique Solutions While the method of substitution works, it is somewhat clumsy when we work with equations involving three or more variables. We will look at a more methodical way of solving a system of equations, called the Gauss-Jordan Elimination Method . Two systems of equations are equivalent if they have the same solution. With the Gauss-Jordan method, we transform a given system into an simpler equivalent system using three operations: 1. Interchanging equations. 2. Multiplying every term of an equation by a constant. 3. Adding/subtracting two equations. Example: Solve the following system: x + y = 16 8 x + 10 y = 146 Subtract 8 times equation (1) from equation (2): x + y = 16 2 y = 18 Multiply equation (2) by 1 2 : x + y = 16 y = 9 Subtract equation (2) from equation (1): x = 7 y = 9 We have solved for x and y , and found one solution to the given system of equations. (Dont forget to check the solution!) What did I do to find my solution? 1. Used an x in the first equation to get rid of the x in the second equation. 1 2. Used the leftover y in the second equation to get rid of the y in the first equation. This same process will work for more than two variables. We will first get rid of the x , then get rid of y , then get rid of z . Example: Find the solution to the given system: x + y + z = 15 x + 3 y + 4 z = 9- x + 2 y- z = 3 Subtract equation 1 from equation 2: x + y + z = 15 + 2 y + 3 z =- 6- x + 2 y- z = 3 Add equation 1 to equation 3: x + y + z = 15 2 y + 3 z =- 6 3 y = 18 Interchange equation 2 and equation 3: x + y + z = 15 3 y = 18 2 y + 3 z =- 6 Multiply equation 2 by 1 3 : x + y + z = 15 y = 6 2 y + 3 z =- 6 Subtract equation 2 from equation 1: x + z = 9 y = 6 2 y + 3 z =- 6 Subtract two times equation 2 from equation 3: 2 x + z = 9 y = 6 3 z =- 18 Multiply equation 3 by 1 3 : x + z = 9 y = 6 z =- 6 Subtract equation 3 from equation 1: x = 15 y = 6 z =- 6 We have found that x = 15, y = 6, z =- 6 is the solution of the given system. Remember to check your answers! We used the x in the first equation to get rid of x in the other equations. We used the y in the second equation to get rid of y in the other equations. We used the z in the third equation to get rid of z in the other equations. The variables really were just placeholders we had all x , y , and z terms lining up vertically. We can use a matrix to reduce the amount of writing we have to do....
View Full Document

This note was uploaded on 02/05/2011 for the course MATH 377 taught by Professor Stephenlang during the Spring '11 term at University of Victoria.

Page1 / 9

2-2 - Chapter 2.2: Gauss-Jordan Elimination Unique...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online